DIALEKTIKA BAHASA JAWA DALAM ADAT PERANG BANGKAT SUKU OSING KECAMATAN SINGOJURUH - Ahmad Sulthoni; Dhalia Soetopo (Universitas Muhammadiyah Purwokerto, 2020)
ABSTRACT Perang Bangkat Ceremony is one proof of the diversity of cultures in Banyuwangi. This custom is held at a bride and groom event at the Osing tribe, but not all wedding gatherings use the Perang Bangkat Ceremony. Perang Bangkat is used when the bride is the eldest and youngest child in her family.The Osing people believe that if the eldest child marries the youngest child, then in his household there will be many problems or temptations that occur. This is where the osing community feels it is necessary to do the Perang Bangkat in the event of a wedding gathering which is intended to keep the obstacles or obstacles in the household that will be lived by the bride and groom. With the above conditions it can be known at this time that very few people understand the Javanese language spoken at the traditional ceremony of the Perang Bangkat. So that in determining the respondents the author uses the snowball method. The data collection used the method of observation, interviews and documentation. From the explanation above, the writer would like to examine further the meaning contained in the Bangkat Customary Ceremony as an effort to increase knowledge about Javanese language and cultural heritage which are intended to increase love and care for the Bangkat Customary Customs in the modernization era. Therefore the authors feel the need to further study the customs of warfare and conduct research with the title "Dialogue of Javanese Language in the Form of Osing Tribal War Sing Singuruh Subdistrict" The method used in descriptive qualitative data analysis with interactive analysis techniques and using the checking of findings by triangulation source. Keywords: Javanese dialectic, Perang Bangkat